Synovial MS4A4A correlates with inflammation and counteracts response to corticosteroids in arthritis - Marie-Astrid Boutet; Irene Mattiola; Rita Silva-Gomes; Alessandra Nerviani; Marina Sironi; Giulia Maria Ghirardi; Alessia Troilo; Stefano Gianoli; Felice Rivellese; Cankut Cubuk; Katriona Goldmann; Anna Rita Putignano; et al. (Proceedings of the National Academy of Sciences, 2025)
MS4A4A belongs to the MS4A tetraspan protein superfamily and is selectively expressed by the monocyte–macrophage lineage. In this study, we aimed to evaluate the role of MS4A4A+ macrophages in rheumatoid arthritis (RA) pathogenesis and response to treatment. RNA sequencing and immunohistochemistry of synovial samples from either early treatment-naïve or active chronic RA patients showed that MS4A4A expression positively correlated with synovial inflammation. Synovial macrophages from patients treated with corticosteroids (CS) exhibited an enhanced expression of MS4A4A and Fc γ receptor (FcγR) 3. Accordingly, CS enhanced in vitro the expression of MS4A4A and FcγR3 in human and murine macrophages. In an experimental model of arthritis, Ms4a4a deletion had no effect on the disease course but was associated with enhanced therapeutic response selectively to CS. These results suggest that macrophage expression of MS4A4A represents a biomarker of joint inflammation in RA and that its upregulation in concert with FcγR3 by CS counteracts the therapeutic activity of these drugs. Macrophage MS4A4A may represent a biomarker of joint inflammation in RA and a target to amplify the therapeutic activity of CS.